A multi-layer security system for data access control, authentication, and authorization - Kaiser, Tamanna; Siddiqua, Rafa; Hasan, Md. Main Uddin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.